Black Stain and Caries in Deciduous and Mixed Dentition. - Bircher, María (Centro de Publicaciones Periódicas Electrónicas de la Universidad Nacional de Rosario, 2008)
The aim of this research was to establish the correlation between dental caries and the black stain, both in deciduous and mixed dentition. A cross-sectional study was practiced to determine the prevalence of chromogenic bacteria in the mouth, and their relationship with teeth pigmentation and caries index. A total of 433 children aged between 3 and 10 years old were examined at the Servicio de Diagnóstico de la Facultad de Odontología de Rosario. The Study group comprised 18 children with black stain while the Control group comprised 18 stain-free children. Dental plaque and saliva samples were taken from both groups and black stain samples were taken from the Study group. All the samples were cultured in specific media for anaerobic pigment-forming bacteria. Variables were established and the data from clinical and dental history, and bacteriologic results was statistically analyzed. The examined population had no obvious evidence of decayed, missing, and filled teeth (DMF-T= 0); however, they suffered from some respiratory disease (bronchial spasm, retropharyngeal mucus and otitis, oral habits like fingersucking, onychophagia and mouth breathing). A correlation was observed between dental caries and black stain; the cultures showed the presence of Prevotella and Porphyromonas, and there was a significant incidence between stained surfaces with respiratory diseases and oral habits.